The Influence of the Use Financial Technology, Owner Financial Literacy, and Risk Tolerance on the Performance of MSMEs in Indonesia - Aeni, Tia Inayatul; Rena, Selsa; Destiana, Rina (IJBLE Scientific Publications Community Inc., 2024)
This study investigates the influence of financial technology adoption, owner financial literacy, and risk tolerance on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Amidst the diverse landscape of Indonesian MSMEs, characterized by challenges in accessing formal financial services, the study examines the role of FinTech in overcoming these barriers and fostering business growth. Additionally, it explores the significance of owner financial literacy in facilitating informed decision-making and the strategic importance of risk tolerance in driving business innovation. Through a quantitative research design and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis, the study offers insights into the nuanced relationships between these factors and MSME performance. The findings provide actionable insights for policymakers, financial institutions, and MSME owners, aiming to promote sustainable MSME development and economic prosperity in Indonesia.